2017
DOI: 10.1016/j.hal.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of Microcystis aeruginosa growth and [D-Leu1] microcystin-LR production in culture media at different temperatures

Abstract: A B S T R A C TThe effect of temperature (26 C, 28 C, 30 C and 35 C) on the growth of native CAAT-3-2005 Microcystis aeruginosa and the production of Chlorophyll-a (Chl-a) and Microcystin-LR (MC-LR) were examined through laboratory studies. Kinetic parameters such as specific growth rate (m), lag phase duration (LPD) and maximum population density (MPD) were determined by fitting the modified Gompertz equation to the M. aeruginosa strain cell count (cells mL À1 ). A 4.8-fold increase in m values and a 10.8-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 76 publications
3
12
0
Order By: Relevance
“…The ratio of the specific growth rate to the lag time duration was approximately constant, suggesting a linear relationship between lag phase and the reciprocal of the growth rate. This finding was corroborated by Crettaz Minaglia [39], who reported that the lag phase showed a linear behavior with the reciprocal specific growth rate for M. aeruginosa. The correlation coefficient (R 2 ) was 0.86.…”
Section: Modeling M Aeruginosa Growthsupporting
confidence: 76%
See 4 more Smart Citations
“…The ratio of the specific growth rate to the lag time duration was approximately constant, suggesting a linear relationship between lag phase and the reciprocal of the growth rate. This finding was corroborated by Crettaz Minaglia [39], who reported that the lag phase showed a linear behavior with the reciprocal specific growth rate for M. aeruginosa. The correlation coefficient (R 2 ) was 0.86.…”
Section: Modeling M Aeruginosa Growthsupporting
confidence: 76%
“…Crettaz Minaglia [39] found that the production of MC-LR decreased with increasing temperature, coinciding with the findings of [43][44][45][46][47][48][49][50].…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations